2019
DOI: 10.1097/rlu.0000000000002806
|View full text |Cite
|
Sign up to set email alerts
|

68Ga–Prostate-Specific Membrane Antigen-11 PET/CT

Abstract: Background Glioblastoma multiforme (GBM) is the most common and most aggressive primary tumor of the brain. After initial therapy and total resection of GBM, 80% to 90% of recurrences occur at the surgical margins. Currently, limited data are available in the literature on the possible use of 68Ga–prostate-specific membrane antigen (PSMA-11) for diagnosis of recurrence in GBM patients. The aim was to assess the feasibility and potential of 68Ga-PSMA-11 PET/CT as a diagnostic procedure in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 20 publications
6
33
2
Order By: Relevance
“…Glioblastoma multiforme (GBM) is the most malignant primary brain tumor with limited treatment options in case of recurrence. Prostate-specific membrane antigen (PSMA) expression was demonstrated in microvascular endothelium of GBM and in vivo confirmed by [ 68 Ga]Ga-PSMA-11 PET/CT in primary as well in recurrence tumor [1][2][3][4]. This knowledge opens a new way for targeted, PSMA-based treatment.…”
mentioning
confidence: 72%
“…Glioblastoma multiforme (GBM) is the most malignant primary brain tumor with limited treatment options in case of recurrence. Prostate-specific membrane antigen (PSMA) expression was demonstrated in microvascular endothelium of GBM and in vivo confirmed by [ 68 Ga]Ga-PSMA-11 PET/CT in primary as well in recurrence tumor [1][2][3][4]. This knowledge opens a new way for targeted, PSMA-based treatment.…”
mentioning
confidence: 72%
“…This result confirms the higher tumour specificity of PSMA compared to FET and it suggests that, in patients with positive tumour uptake, 68 Ga-PSMA-617 has a greater clinical potential than 18 F-FET and 18 F-FDG as a tracer for the visualisation of recurrent tumour lesions and for secondary treatment planning. It is worth noting that this observation not only is in agreement with the observations reported in recent studies of recurrent GBM patients, 321,322,326 but also adds value to the literature of case studies reporting the value of 68 Ga-PSMA as a better PET tracer than FDG for the diagnosis, monitoring and treatment planning for primary GBM lesions. 319,331 The results obtained with the mirror-image method were validated by using a second method for the selection of the background activity reference in the contralateral normal brain.…”
Section: Feature Extractionsupporting
confidence: 90%
“…330 The values of PSMA TBRmean and TBRmax are within the range of values previously determined with the 68 Ga-PSMA-11 tracer by Sasikumar et al 321,322 (median TBRmax = 14.4,; n = 9), but much lower than the values recently determined by Kunikowska et al 326 (median TBRmax = 96.7,n = 15). The lower values obtained in the present study compared to those reported in the study published by Kunikowska et al 326 might be explained both by the different method for background activity region selection and, most importantly, by the slower tumour accumulation of 68 Ga-PSMA-617 compared to 68 Ga-PSMA-11. 323 The lack of reported TBRmean values in previously published studies limits a more thorough comparison, given that this parameter is considered more indicative than TBRmax.…”
Section: Feature Extractioncontrasting
confidence: 90%
See 2 more Smart Citations